Managing ASD pupils’ challenging behaviour: a case study - Roslan, Samsilah; Azizan, Che Rozaniza; Othman, Azraai; Abdul Rahim, Nadia; Wan Ramli, Wan Faridah Fairus; Sulaiman, Noor Aslina; Zainal, Hasny @ Yanti (Universiti Putra Malaysia Press, 2017)
Autistic Spectrum Disorder (ASD) pupils are given equal access to primary and secondary education, but coping with their challenging behaviour may require teachers’ involvement. Studies documented that ASD pupils struggle to meet the demands of their school environment due to several challenges in physical, intellectual, social and emotional (PISE) aspects. Hence, recognizing and managing their challenging behaviours crucial for enhancing their participation in the classroom. This case study aimed to explore ASD pupils’ challenging behaviour, teachers’ approaches in managing these behaviour and effective strategies to maximize pupils’ classroom participation. Samples of 6 ASD pupils undergoing Special Education Integrated Program and 3 special education teacher from 3 selected schools in Malaysia were purposely selected. Observation protocol, field notes and documents analyses were used to gain the research data. Thirty minutes of daily observationsin four consecutive weeks were conducted during the classroom teaching and learning. Emerging themes and researcher’s impressions were documented. Findings indicated that in terms of PISE, ASD pupils engaged in various types of challenging behaviours. The implementation of reward system, antecedent-behaviour-consequences (ABC), and teacher-parent partnership were able to promote positive behaviour in the classroom. ASD pupils’ classroom participation were also maximized through simplified instruction, interest-based learning activities, task analysis, multisensory approach and engaging classroom activities. To conclude, this case study contributes into the understanding of how teachers’ common practices may help to overcome ASD pupils’ challenging behaviour; thus leading to active classroom participation.